2008
DOI: 10.1161/strokeaha.107.513143
|View full text |Cite
|
Sign up to set email alerts
|

‘Hip-Hop’ Stroke

Abstract: Background and Purpose-Public stroke recognition is poor and poses a barrier to acute stroke treatment. We describe a stroke literacy program that teaches elementary school children in high-risk communities to recognize stroke and form an urgent action plan; we then present results of an intervention study using the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 24 publications
(21 reference statements)
2
85
0
Order By: Relevance
“…As some ethnic groups are at higher risk of stroke, this also supports existing research demonstrating that those at higher risk of stroke have worse understanding. 7,10,17,20 Previous studies found that lower education levels linked with worse general understanding of stroke. 7,10,16 The results from this study did not show a similar statistically significant trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As some ethnic groups are at higher risk of stroke, this also supports existing research demonstrating that those at higher risk of stroke have worse understanding. 7,10,17,20 Previous studies found that lower education levels linked with worse general understanding of stroke. 7,10,16 The results from this study did not show a similar statistically significant trend.…”
Section: Discussionmentioning
confidence: 99%
“…16,20 These showed good short-term knowledge improvement, but were 'one-off ' interventions. A recent systematic review of media campaign effectiveness found these are helpful in awareness raising but less so in changing behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…We imputed missing responses as incorrect. 2 tests were used for all comparisons except the composite score for which a two-sample t test was used. All analyses were conducted using SAS version 9.2 (SAS Institute Inc., Cary, NC).…”
Section: Settingmentioning
confidence: 99%
“…1 Programs targeting children may equip them with the ability to recognize stroke symptoms and call 911, [1][2][3] but long-term follow-up data are scarce. Interventions have engaged elementary and middle school children, with program follow-up duration ranging from 10 days 4 to 2 months.…”
mentioning
confidence: 99%
“…Such unsatisfactory result is predictable because "FAST" is specifically designed for those who can understand English, and thus, developed across the world due to the effectiveness of "FAST" in reducing prehospital delay and increasing emergency medical service system utilization. [16][17][18] In the recent SWIFT PRIME Multi-center Randomized Controlled Trial, the median time from the stroke symptom onset to arrival at the emergency department was less than 2 hours (109·5 min with interquartile range of 54-192.5 min). [19] Rapid stroke recognition with immediate triggering of medical emergency service played significant role.…”
mentioning
confidence: 99%